1982
DOI: 10.1212/wnl.32.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoseizures

Abstract: A prospective study of pseudoseizures using prolonged video-electroencephalographic (EEG) recording was carried out in 60 patients. Of 33 patients with episodes of uncertain mechanism, a diagnosis based on recorded episodes was made in 18 (55%). Twelve (36%) had pseudoseizures; 6 (18%) had epileptic seizures. Ten additional patients had epileptiform EEGs compatible with epilepsy. Of 27 patients with presumably uncontrolled epileptic seizures, 4 (15%) had recorded pseudoseizures. Prediction of the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
1
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(96 citation statements)
references
References 0 publications
5
85
1
5
Order By: Relevance
“…One patient with presumptive diagnosis of frontal lobe complex partial seizures was included in the category of possible seizures because of lack of any EEG changes during the stereotypical events. The clinical characteristics of the events were suggestive of frontal lobe complex partial seizures, which are sometimes difficult to distinguish from the PNESs (16,18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One patient with presumptive diagnosis of frontal lobe complex partial seizures was included in the category of possible seizures because of lack of any EEG changes during the stereotypical events. The clinical characteristics of the events were suggestive of frontal lobe complex partial seizures, which are sometimes difficult to distinguish from the PNESs (16,18).…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians had no access to the patient's responses to the questionnaires when making the final diagnosis. Although the clinical features and neuropsychological profile of the patient may by suggestive of the diagnosis of PNESs, the final diagnosis can be confirmed only by simultaneous video recording of the clinical behavior and with EEG (15,16,18). Therefore the diagnosis of PNESs versus ESs in all patients included in this study is based on the results of the prolonged video-EEG monitoring (PVEM), the clinical characteristics of the events recorded, and other supporting evidence (e.g., neuropsychological testing/MMPI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study 31 conducted for an average of 12 weeks and which included 16 patients, the authors found cessation of seizures in 9 (56.2%) patients. King et al 32 treated 14 patients and reported effectiveness in the cessation and improvement of seizures at 79%. The educational approach has also been indicated 33 as a form of support and assistance for patients, aimed at accepting the psychological nature of their symptoms and the need for psychological monitoring.…”
Section: Resultsmentioning
confidence: 99%